A Review of Academic Research on Entrepreneurship Skills Applying Citation Analysis : Identification of Clusters and Themes - Dwivedula, Ravikiran; Chakrabarti, Diganta (AMC Indian Journal of Entrepreneurship, 2020)
The purpose of this paper was to categorize the literature on entrepreneurial skills using citation analysis. We analyzed 206 peer-reviewed articles sourced from Web of Science applying Citnet Explorer. Five clusters were revealed from the analysis on the basis of underlying idea or theme in each. We named them entrepreneurial motivation, transforming institutional structures, entrepreneurship education, entrepreneurial thinking, and entrepreneur-firm relations. Through this paper we argued that in order to better understand essential skills for entrepreneurs, each of these five themes need to be taken into account as they have a bearing on both the individual’s disposition and the larger entrepreneurial ecosystem.